Avaliação citotóxica, metabólica e genotóxica em ratos Wistar tratados com Morinda citrifolia, L. - Riffel, Juliana de Brazil (2017)
Morinda citrifolia L., as known as noni, is widely used in alternative medicine for various purposes. However, the biological effects of its pulp are still very controversial. Therefore, the objective of this study was to evaluate cytotoxic, metabolic and genotoxic effects, in rats treated with Morinda citrifolia L. The fruits were harvested in the spring period, and the pulp was obtained without seeds. To perform the cytotoxicity test of hemolytic activity, 1 mL of rat whole blood was randomly collected and serial dilutions were performed with decreasing concentrations of the extract, starting with 100 mg/mL and ending with 0.01953 mg/mL. For the metabolic and genotoxic analyzes, experimental groups of male rats were used (n=7 each group). The treatment period was 15 consecutive days, and control groups orally received 3.0 mL of tap water and treated groups received mL of Morinda citrifolia pulp (243 mg/day/rat). Weekly, body weight, food intake, energy intake and blood glucose were measured and on the 14th day, the oral glucose tolerance test (OGTT). On the 15th day, the rats received intraperitoneal saline solution (NaCl 0.9%) or cyclophosphamide (CPA 25mg/Kg) according to the treatment group. On the 16th day, body weight gain was estimated, as well as blood collection for biochemical measurements and collection of bone marrow cells for the micronucleus test. The results show cytotoxic activity of the extract in most serial dilutions. Regarding the metabolic parameters, there was no negative effect on the animals' organisms, also presenting a hypoglycemic action. For genotoxic analysis, a biphasic behavior of the pulp was observed, which exerted both mutagenic and antimutagenic activity. Thus, it can be concluded that the treatment with Morinda citrifolia L. is still controversial, not being recommended freely for use by the population.